Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $a,b,c$ be roots of equation $x^3-6x^2+kx+k=0$,and $(a-1)^3+(b-2)^3+(c-3)^3=0$.

how to compute $a,b,c,k=?$

if we do work equivalently as to find out the solution: $$\begin{align*}(1)&abc=&-k\\(2)&ab+ac+bc=&k\\(3)&a+b+c=&6\\(4)&(a-1)^3+(b-2)^3+(c-3)^3=&0\end{align*}$$

Is there good skill?

share|cite|improve this question
Interesting question (+1) – user 1618033 Feb 7 '13 at 11:01
up vote 1 down vote accepted

We have $a+b+c=6, ab+ac+bc=k, abc=-k, (a-1)^3+(b-1)^3+(c-1)^3=0$.

Thus $(a+1)(b+1)(c+1)=abc+(ab+ac+bc)+(a+b+c)+1=k+(-k)+6+1=7$.

Substitute $x=a-1, y=b-2, z=c-3$, so $x+y+z=x^3+y^3+z^3=0, \, (x+2)(y+3)(z+4)=7$.

Note that conversely any $x, y, z$ satisfying these equations will in turn give unique $a, b, c$ satisfying $a+b+c=6, (a-1)^3+(b-2)^3+(c-3)^3=0, (a+1)(b+1)(c+1)=7$, so that $abc+ab+ac+bc=(a+1)(b+1)(c+1)-(a+b+c+1)=7-6-1=0$. Now from the values of $a, b, c$, we can then uniquely determine $k$.

Now $x^3+y^3=-z^3=(-z)^3=(x+y)^3$, so $0=3xy(x+y)=-3xyz$.

Thus at least 1 of $x, y, z$ is 0.

If $x=0$, then $z=-y$, so $2(y+3)(4-y)=7$, so $2y^2-2y-17=0$, giving $y=\frac{1 \pm \sqrt{35}}{2}$.

We have $(x, y, z)=(0, \frac{1 \pm \sqrt{35}}{2}, -\frac{1 \pm \sqrt{35}}{2})$.

If $y=0$, then $z=-x$, so $(x+2)(3)(4-x)=7$, so $3x^2-6x-17=0$, giving $x=\frac{3 \pm \sqrt{60}}{3}$.

We have $(x, y, z)=(\frac{3 \pm \sqrt{60}}{3}, 0, -\frac{3 \pm \sqrt{60}}{3})$.

If $z=0$, then $y=-x$, so $(x+2)(3-x)(4)=7$, so $4x^2-4x-17=0$, giving $x=\frac{1 \pm \sqrt{18}}{2}$.

We have $(x, y, z)=(\frac{1 \pm \sqrt{18}}{2}, -\frac{1 \pm \sqrt{18}}{2}, 0)$.

Thus $(a, b, c)=(1, 2+\frac{1 \pm \sqrt{35}}{2}, 3-\frac{1 \pm \sqrt{35}}{2}), (1+\frac{3 \pm \sqrt{60}}{3}, 2, 3-\frac{3 \pm \sqrt{60}}{3}), (1+\frac{1 \pm \sqrt{18}}{2}, 2-\frac{1 \pm \sqrt{18}}{2}, 3)$.

Edit: Calculating values of $k$ using $k=-abc$ now gives $(a, b, c, k)=(1, 2+\frac{1 \pm \sqrt{35}}{2}, 3-\frac{1 \pm \sqrt{35}}{2}, \frac{5}{2}), (1+\frac{3 \pm \sqrt{60}}{3}, 2, 3-\frac{3 \pm \sqrt{60}}{3}, \frac{16}{3}), (1+\frac{1 \pm \sqrt{18}}{2}, 2-\frac{1 \pm \sqrt{18}}{2}, 3, \frac{27}{4})$.

share|cite|improve this answer



You may want to read about Viéte's formulae , too.

share|cite|improve this answer
I know this theorem. but also hard to find out the solution. – Leitingok Feb 7 '13 at 11:31
Did anyone promise you easy work in mathematics? Because if someone did then he/she/they lied to you. At least here you have an idea to begin working, so downvoting the answer seems a little too harsh, doesn't it? – DonAntonio Feb 7 '13 at 11:51
I mean this meathod is not easy without using software such as matlab. – Leitingok Feb 7 '13 at 11:53
Yes... so? Spend some time making some calculations, what's the big deal?! For example $$a^3+b^3+c^3=\left(a+(b+c)\right)^3-3a^2(b+c)-3a(b+c)^2-3b^2c-3bc^2=$$ $$=\left(a+b+c\right)^3-3\left(a(ab+ab+bc)+b(ab+ac+bc)\right)\ldots\;\;etc.$$ – DonAntonio Feb 7 '13 at 12:05
not this.I did some work that you give me. but it's not easy to use in $(a-1)^3+(b-2)^3+(c-3)^3$ – Leitingok Feb 7 '13 at 12:12

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.